1996
DOI: 10.1021/jp960376s
|View full text |Cite
|
Sign up to set email alerts
|

Dealumination of Zeolite β via Dicarboxylic Acid Treatment

Abstract: It is demonstrated that zeolite β and zeolite β containing catalysts can be dealuminated to very low acidity levels using a novel oxalic acid treatment without reducing zeolite integrity. The effect of the oxalic acid treatment has been studied over a wide range of treatment conditions for both silica-bound and unbound zeolite β catalysts. Greater than 90% dealumination is observed with a concomitant reduction in n-hexane-cracking activity as measured by the alpha (α) test. Removal of framework aluminum occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
92
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 12 publications
7
92
0
Order By: Relevance
“…Dealumination of zeolite beta using oxalic acid and citric acid has been reported [14,15]. It also have been reported that aluminum species in the solution, which are eliminated from the framework by HCl treatment, are easily reinserted into the framework by controlling the pH value of the solution [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dealumination of zeolite beta using oxalic acid and citric acid has been reported [14,15]. It also have been reported that aluminum species in the solution, which are eliminated from the framework by HCl treatment, are easily reinserted into the framework by controlling the pH value of the solution [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been achieved by hydrolysis of Al-O-Si bonds by mineral acids combined with steaming [7][8][9][10][11], complexation of aluminum with organic acids such as oxalic acid, citric acid or organic sulfonic acid [12][13][14][15], or by direct replacement of aluminum by silicon with gaseous silicon tetrachloride [16]. It has been reported that the zeolites structure, the Si/Al ratio of the framework, the crystal size, and the number of acid sites interacting with the framework or the number of defect sites influence the dealumination behavior of an individual zeolite sample [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Furthermore, we have used oxalic acid as a catalyst in our previous study for the synthesis of dihydropyrimidine 2-(1H)-ones, 31 2-aryl-1-arylmethyl-1H-benzimidazoles and 2,4,5-triaryl-1H-imidazoles, 32 quinazolin-4(3H)-ones 33 and coumarins. 34 In order to explore the use of oxalic acid catalyst further, herein we report the synthesis of 1, 5-benzodiazepines from o-phenylene diamine and various α, β-unsaturated ketones.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature it is known that NFAl species that are created during synthesis or calcination can be removed by a mild treatment using oxalic acid. [28,29] Therefore, part of the HMOR sample was treated in an aqueous solution of 0.1m oxalic acid at 353 K for 1 h. The sample was then filtered, washed, dried at 353 K for 12 h, and calcined as described before. This treatment was executed twice to give a sample that is referred to as HMOR-ox.…”
mentioning
confidence: 99%